ChemInform Abstract: O‐Alkylation of 3‐Hydroxyisoxazoles Predominates under Mitsunobu Conditions. Issue 32 (12th August 2014) - Chen, Lijia; Fletcher, Steven
Abstract: The Mitsunobu reaction of 3‐hydroxyisoxazoles with a range of alcohols is investigated with respect to selective O‐alkylation.